Legislasi dan keadilan sosial: Mewujudkan UU yang berkeadilan sosial melalui pengujian konstitusionalitas UU di Mahkamah Konstitusi RI - Azed, Abdul Bari (2011)
After amendments were made to the 1945 Policy Laws of the Republic of Indonesia from 1999 to 2002, a very significant change in the structure of polity took place in the Republic of Indonesia.One of the most obvious changes was the direct election of the President and Acting President and the formation of the Constitutional Court in accordance with 2003 Law Number 24 regarding the Constitutional Court of the Republic of Indonesia.One of the duties of the Constitutional Court is to undertake an application process for reviewing any law opposed to the 1945 Policy Law (constitutional review).This article can explain how the constitutional review process is one of the existing features of control, and also checks and balances among the branches of state power.A constitutional review differs from a judicial review.The judicial review is wider in scope than the constitutional review.The objects reviewed by a judicial review not only identify legal products related to law, but also cover law regulations.According to Jimmy Asshiddiqie, former Chief of the Constitutional High Court of the Republic of Indonesia, this mechanism of constitutional review is accepted as the way modern laws of countries widely control the subjects reviewed with respect to the authority given to the relevant board under the Policy Laws of a particular country.